Using the Snowball Throwing Cooperative Learning Model to Improve Motivation and Thematic Learning Outcomes - Efa Nurfitri; Suroyo Suroyo (Peneliti.net, 2020)
The Snowball Throwing type of cooperative learning model is expected to make students active, feel happy and work together so that problems can be solved easily and correctly. In Snowball Throwing students develop their knowledge through the act of explaining the material to their friends who do not understand. Meanwhile, students who do not understand the material can be more familiar with the explanations given by their friends. This is in accordance with the main idea of ​​learning motivation, namely learning motivation is everything that can motivate students to learn. So that each individual gets the benefits and learning outcomes of this group. The purpose of this study was to determine the effect of using the Snowball Throwing learning model on increasing motivation and thematic learning outcomes in fifth grade students of SD Harapan Indonesia. The results showed that there was an effect of the Snowball Throwing type cooperative learning model on increasing motivation and learning outcomes of thematic subjects in fifth grade students of SD Harapan Indonesia.